2016
DOI: 10.1016/j.jcrs.2015.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Nonpenetrating femtosecond laser intrastromal astigmatic keratotomy in eyes having cataract surgery

Abstract: Dr. Day was supported by the National Institute for Health Research (NIHR) Biomedical Research Centre based at Moorfields Eye Hospital NHS Foundation Trust and UCL Institute of Ophthalmology. Dr. Stevens has been a consultant to Optimedica Inc., now part of Abbott Medical Optics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 20 publications
6
51
1
Order By: Relevance
“…This analysis revealed a trend to undercorrection, with a mean DV value of 0.57 ± 0.34 D 3 months postoperatively. This trend has been also reported in previous studies [13] [16]. In our series, this trend to undercorrection was maintained during the 12-month follow-up.…”
Section: A Kaczmarek Et Al Open Journal Of Ophthalmologysupporting
confidence: 92%
See 3 more Smart Citations
“…This analysis revealed a trend to undercorrection, with a mean DV value of 0.57 ± 0.34 D 3 months postoperatively. This trend has been also reported in previous studies [13] [16]. In our series, this trend to undercorrection was maintained during the 12-month follow-up.…”
Section: A Kaczmarek Et Al Open Journal Of Ophthalmologysupporting
confidence: 92%
“…Comparable to our study, Löffler et al [8] have recently reported a reduction of the magnitude of anterior corneal astigmatism in a prospective study enrolling 27 healthy corneas undergoing penetrating femtosecond laser-assisted keratotomy, with minimal effect on the magnitude of posterior corneal astigmatism. Chan et al [11] The reduction in corneal topographic astigmatism was associated with a reduction in refractive cylinder, as observed in other studies evaluating the effect of femtosecond-assisted ISAK in virgin [13], post-refractive surgery [18], and post-keratoplasty corneas [9] [10] [15]. Day and colleagues [13] found in a prospective case series including 196 eyes undergoing femtosecond laser-assisted ISAK that 0% of the eyes had a refractive cylinder of 0.50 D or less preoperatively, with an increase to 32.1% postoperatively.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In the study that compare multifocal toric IOL and multifocal IOL with LRI, the toric IOL still showed more predictable than LRI in multifocal IOLs [16]. Recently, LRI can also be performed by Femtosecond laser in laser assisted cataract surgery [17,18]. Despite the accuracy of the optical coherence tomography-guided LRI with femtosecond laser, there was a case report of corneal perforation [19].…”
Section: Introductionmentioning
confidence: 99%